KAJIAN ASPEK LINGKUNGAN PEMANFAATAN AGREGAT TAILING ModADA SEBAGAI MATERIAL BIDANG JALAN - Anisa Putri Triana; Gugun Gunawan; Pamahayu Prawesti; Sugiyono - (Direktorat Bina Teknik Jalan dan Jembatan, 2021)
The sustainable development concept encourages industrial and business sectors to manage their waste, one of it is the utilization of tailing as infrastructure raw materials for road, bridge, and building. Tailing is included in the category of B3 waste which requires careful handling related to the safety aspect for environment and living beings for its advance used as regulated in PP No 101/2014 and/or PP No 22/2021. This paper examines the characteristics of ModADA tailing aggregate materials from environmental aspect, as one of the materials mixed with tailing and has potential as a raw material for infrastructure in Indonesia. The environmental aspect testing is carried out through TCLP and total metal test. The test result showed the presence of heavy metal content and mercury metal (Hg) concentration in the ModADA tailings material aggregate of 0.570 - 0.825 mg/kg (as for the quality standard threshold for the total metal content of Hg-TK C in PP 101/2014 and PP 22/2021 by 0.3 mg/kg). Considering the possibility of heavy metal toxicity (acute and chronic), it is needed to create an environmental management policy that regulates the utilization of ModADA tailing aggregate material in the cycle of road construction cycle. Keywords: Tailing, ModADA Tailing Aggregate Material, Environtmental, TCLP, Heavy Metal Toxicity